A need for direct contact with particle surfaces in the bacterial oxidation of covellite in the absence of a chemical lixiviant - Pogliani, C. (1990)
For bio-leaching, direct contact is needed between Thiobacillus ferrooxidans and covellite (CuS) which oxidizes by a direct mechanism.